Por entre encontros e saberes: a formação docente em diálogo com o "Poder Escolar" e o pensamento freiriano - Dall'igna, Maria Antonieta (2012)
This study deals with teacher education which results from the participation in the Encontro sobre o Poder Escolar, a periodical event that has been held in Pelotas, RS, Brazil, since 2001. This meeting, which aims at developing and valuing professionals in Education, has been collectively sponsored and organized by different institutions. The presuppositions that have supported its planning are the recognition of teachers knowledge, the importance of dialogue and collective work in teacher education and the reflective action in teachers practices. The meeting, which has had a diverse program with conferences, panels, cultural activities, has also comprised Round Tables to Share Experiences, which have made teachers play the main roles in their development. Proposals have been open-ended so that the meeting can be re-constructed every year by introducing new activities and other actors, such as students and parents. The critical reflection upon a project that has been held for so long and has involved a large number of people resulted from an initial question: how do the Encontros sobre o Poder Escolar affect the school practices of the teachers who take part and present their experiences in these meetings? The need to set limits in th investigation led me to focus data collection on the reports of teachers who had presented their experiences. Data were collected by documents and consolidated by meetings with focal groups. The investigation had the characteristics of a case study whereas data interpretation respected the principles of content analysis. The dialogue with Freire s thoughts enabled me to find the dimensions of the concept of permanent education, such as development as a change, critical reflection upon practice and dialogue, in the Encontro sobre o Poder Escolar.